ST-Elevation Myocardial Infarction in the Presence of Septic Shock - Leah Ishmael; Joseph Zalocha (Case Reports in Critical Care)
Elevated cardiac enzymes are often seen in the setting of sepsis. The mechanism involves hypoperfusion and possible compromise to myocardial tissue. Electrocardiogram (ECG) changes in the setting of septic shock are less common and can vary widely. Rarely, ST-segment elevations can occur. This case describes a 54-year-old female who presented with septic shock secondary to pyelonephritis and Escherichia coli bacteremia. The patient was admitted to the intensive care unit on norepinephrine and required mechanical ventilation. A significant rise in troponin I (peak 19.8 ng/mL) was seen and ECG showed ST-segment elevations in leads I and aVL with reciprocal ST depressions in leads II, III, and aVF. The patient was taken urgently for left cardiac catheterization, which showed no evidence of obstructive coronary artery disease. When distinguishing between septic shock and cardiogenic shock, insertion of a pulmonary artery catheter may help with diagnosis and treatment of cardiogenic shock. Catheter hemodynamic monitoring can also confirm the diagnosis. In our patient’s case, hemodynamic monitoring was initiated and was not consistent with cardiogenic shock. ST-segment elevations in the high lateral leads and elevated cardiac markers were likely due to severe transmural ischemia secondary to increased oxygen demand. The patient was continued on intravenous antibiotics for treatment of her septic shock. She was extubated and weaned off of norepinephrine within 48 hours. Repeat ECG performed after resolution of the infection showed normal sinus rhythm with no ST-segment changes. Cardiac dysfunction in the setting of septic shock is well described in medical literature; however, the mechanisms of dysfunction are not explicitly understood. Transient hypoperfusion, coronary vasospasm, and localized endothelial damage are possible components. It is important to think of varying etiologies, other than acute coronary syndrome when approaching patients in septic shock with acute ST-segment changes and elevated cardiac markers.